2011
DOI: 10.1111/j.1742-481x.2011.00838.x
|View full text |Cite
|
Sign up to set email alerts
|

Early use of negative pressure therapy in combination with silver dressings in a difficult breast abscess

Abstract: Combining silver-based dressings with negative pressure therapy after radical excision of chronically infected breast disease is a novel application of two technologies. One patient with complex, chronic, infected breast disease underwent radical excision of the affected area and was treated early with a combination of silver-based dressings and topical negative pressure therapy. The wound was then assessed sequentially using clinical measurements of wound area and depth, pain severity scores and level of exud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 19 publications
(23 reference statements)
0
14
0
Order By: Relevance
“…NPWT used for wound healing is a noninvasive technology that promotes healing. It is based on the application of mechanic stress on the tissues, which leads to an increase of angiogenesis and healthy granulation tissue in a wet environment, which in turn favors the elimination of non‐viable tissue and exudate . Also, the inpatient/hospitalized associated costs are reduced by the use of the therapy via outpatient treatment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…NPWT used for wound healing is a noninvasive technology that promotes healing. It is based on the application of mechanic stress on the tissues, which leads to an increase of angiogenesis and healthy granulation tissue in a wet environment, which in turn favors the elimination of non‐viable tissue and exudate . Also, the inpatient/hospitalized associated costs are reduced by the use of the therapy via outpatient treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the inpatient/hospitalized associated costs are reduced by the use of the therapy via outpatient treatment. However, NPWT may be associated with complications, mostly hemorrhage or infection . Some studies have associated the use of NPWT with an increase in the bacterial load …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Silver dressings have also been described to promote healing of diabetic foot ulcers, and to prevent re-infection of skin ulcers after debridement [68,69]. Two case studies were found illustrating the successful wound healing achieved when NPWT is combined to silver dressings; one post-debridement for necrotizing fasciitis, and the other after radical excision of a difficult breast abscess [70,71]. The exact mechanisms by which silver promotes healing are not fully understood, and research shows mixed results.…”
Section: Discussionmentioning
confidence: 96%